2013
DOI: 10.3126/jcmc.v3i3.8633
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Profile of Urinary Tract Infection of Children at GMC Teaching Hospital

Abstract: This study aimed to find bacterial profile of urinary tract infection (UTI) in children between 2 months to 15 years of age. This is a hospital based retrospective study conducted at Gandaki medical college and teaching hospital, Pokhara over a period of 18 months. Among the total 575 children enrolled for the study, 110 children (19.1%) were found to be culture positive. Most common age group having culture positivity is 1-5 years (40%). Present study showed that UTI is more common in girls (69.1%) than in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 18 publications
(11 reference statements)
2
16
1
Order By: Relevance
“…This is in complete agreement to the findings in two studies done in Nepal and another Bangladeshi study. 2,9,22 This was less than the finding observed by GK Rai et al (93.3%) among children of Nepal. 21 In different studies, the percentage of Escherichia coli (E. coli) was different ranging from 30.2% to 90% in collected urine samples.…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…This is in complete agreement to the findings in two studies done in Nepal and another Bangladeshi study. 2,9,22 This was less than the finding observed by GK Rai et al (93.3%) among children of Nepal. 21 In different studies, the percentage of Escherichia coli (E. coli) was different ranging from 30.2% to 90% in collected urine samples.…”
Section: Discussioncontrasting
confidence: 56%
“…21 In different studies, the percentage of Escherichia coli (E. coli) was different ranging from 30.2% to 90% in collected urine samples. 2,10,11,12 In this study, E. coli was followed by Enterococcus (19.2%), Klebsiella (10.2%) and others as shown in Table 3. This is in close agreement with a previous study reported by Ladhini and Grandsen.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations